Comparison of elemental composition and 87Sr/86Sr-143Nd/144Nd between fossil and modern fish teeth and the significance of the enrichment of REE in deep-sea sediments - Xu, Zhijie; Zhang, Xiaoyu; Zhu, Kongyang; Huang, Mu; Yu, Miao; Li, Zheng; Qiu, Zhongrong; Lu, Yanfang (Frontiers in Marine Science, 2025)
Fossil fish teeth are important carriers of rare earth elements (REEs) in deep-sea sediments. Meanwhile, 87Sr/86Sr-143Nd/144Nd in these fossils have been widely used in paleoceanography. However, when and how REEs enter the fish teeth remains ambiguous, which hinders elucidating the enrichment mechanism of REEs in deep-sea sediments, and the effectiveness of 87Sr/86Sr-143Nd/144Nd in paleoceanography is doubted. This study examined the contents of REEs, major and trace elements, and 87Sr/86Sr-143Nd/144Nd in modern fish teeth and in fossil fish teeth from deep-sea sediments. The results indicated that elemental geochemical properties and a redox environment are the main factors controlling their enrichment process in fish teeth. At least three categories of trace elements are classified during two different stages (physiological process of living fish and post-deposition of fossils): (1) elements of Type I mainly belong to IA, IIA, IIIA, IVA, and transition group with active chemical properties, entering into the fish teeth during life; (2) Type II represents elements from the IA, VA, transition elements, and Actinides groups, and are enriched uninterruptedly from the living fish teeth to the post-deposition fossils with variable valences under different redox conditions; (3) Type III are elements accumulated only after deposition under oxidizing or suboxidizing and are members of Lanthanides and rare dispersed elements groups with a large atomic radius and strong chemical activity. The distinctly different enrichment processes of Sr and Nd, 87Sr/86Sr, and 143Nd/144Nd in fossil fish teeth may represent different material sources and should be cautiously employed in paleoceanography. The continuous rehabilitation of 87Sr/86Sr in fossil fish teeth after deposition would change the original 87Sr/86Sr of seawater recorded near fish teeth but the content of Sr remains unchanged. As for 143Nd/144Nd, when Nd enters the fossils after deposition, the exchange of 143Nd/144Nd between particles and pore liquid gradually ceases due to the saturation of the isomorphism lattice. 143Nd/144Nd of fossil fish teeth may provide more information about deep seawater at the seawater-sediment interface. This study elucidates the enrichment mechanism of REEs in deep-sea sediments and the cautious utilization of 87Sr/86Sr and 143Nd/144Nd of fossils is a prerequisite.